Penerapan Sparing Dalam Menunjang Implementasi Smart City Di Kota Denpasar - Maria Atalya Angelus Leza; I Putu Satwika (Primakara University, 2022)
The significant increase in population density has resulted in an increase in the amount of waste and waste generated in cities. The origin of this waste disposal varies, some from factory waste and some from household waste. Factory waste water can cause water pollution, causing the water to become cloudy and smell bad, the water becomes unclean and becomes a breeding ground for disease, the ecosystem around the water is disturbed, and the land around the factory where residents live is polluted by wastewater, so they face problems. disease and many other negative effects. The problem of water contaminated with waste is quite common in Bali, especially in the city of Denpasar. The waste comes from industrial waste and also from tofu factory waste. The solution given is the SPARING system. SPARING is a Continuous and Online Wastewater Quality Monitoring System designed to monitor the quality of wastewater treatment. Based on Internet of Things (IoT) technology, the system can monitor and control waste quality in real time and at low cost.